The Effectiveness of Reading Folk Literature in Improving English Language Learners’ Reading Proficiency in Elementary Grades - Mariwan Hwayyiz Rustum (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aims at investigating the effectiveness of reading popular literature in improving reading proficiency among English language learners in primary grades. English language learners Face difficulty in comprehension problems and difficulty in mastering the skill of reading in the English language, and thus it reflects on their self-feeling negatively. The researcher uses reading popular literature as a means of improvingeading proficiency among English language learners in primary grades and demonstrates its effectiveness. The skill of reading was chosen exclusively because it is one of the most important basic skills in English language on which all other skills depend. the researcher dealt with an explanation of this effectiveness to enhance the skill of reading, then dealt with a group of previous studies that were examined, and later the researcher mentioned the advantages that result from using reading folk literature as a means of improving skills in English language among primary school students. he researcher concludes his study with some recommendations that work to increase the effectiveness of reading popular literature and improve the skill of reading in general